Leaching of Lead, Chromium and Copper into Drinks Placed in Plastic Cups at Different Conditions - Ahimbisibwe, Oliver; Byamugisha, Denis; Mukasa, Paul; Omara, Timothy; Ntambi, Emmanuel (American Journal of Analytical Chemistry, 2022)
Plastic cups commonly used by communities of Uganda lose color with time as they are used. The purpose of this study was to determine the concentrations of copper, lead and chromium in drinks placed in blue and green plastic cups from two companies (anonymized as A and B) in Uganda. New blue and green polyethylene plastic cups produced from unrecycled material were purchased from company A and company B while control cups of Luminarc white (Saudi Arabia) and porcelain white glazed (China) were purchased from shops in Mbarara city. The ash from the burnt blue and green plastic cups was digested using Aqua Regia . After a holding time of 30 and 60 minutes, milk and tea samples in the four different cups were also digested using Aqua Regia . Sample analysis for the supernatants was done in triplicates using an atomic absorption spectrophotometer. The ash of blue and green cups from company A was found to contain the highest concentration of heavy metals which ranged from 0.73 to 1.86 ppm for lead, 8.05 to 38.32 ppm of copper, and 655.80 to 756.57 ppm for chromium. For company B, the heavy metal concentrations ranged from 0.76 to 1.43 ppm, 5.51 to 22.85 ppm, and 756.67 to 815.25 ppm, respectively. The concentration of the leached metals ranged from 0.001 to 5.75 ppm for copper, 0.001 to 0.60 ppm for chromium, and 0.001 to 0.41 ppm for lead for the cup of company A. For the cup from company B, the concentration ranges for the leached metals were from 0.001 to 3.59 ppm, 0.001 to 1.08 ppm, and 0.001 to 0.29 ppm, respectively. Most of the values obtained for the leached concentrations of the metals studied were above the respective drinking water in WHO and USEPA permissible limits of 1 ppm (copper), 0.05 ppm (lead) and 0.1 ppm (chromium). The blue and green plastic cups from both companies had leached concentrations of copper, lead and chromium below the permissible limits at 25˚C, pH 6.2 (milk) and a holding time of 30 minutes. The control cups did not leach detectable amounts of copper, chromium and lead under the study conditions, hence it may be safe for holding the hot drinks at the temperatures experimented in this study
Keywords: Plastic Cups; Leaching; Metal Concentration